2015
DOI: 10.12820/rbafs.v.20n2p141
|View full text |Cite
|
Sign up to set email alerts
|

Tendências dos indicadores de atividade física em adultos: Conjunto de capitais do Brasil 2006-2013

Abstract: <p class="MsoBodyText" style="margin-top: 6.0pt; margin-right: 0cm; margin-bottom: .0001pt; margin-left: 0cm; text-align: justify; line-height: 200%;">Descrever as tendências temporais dos indicadores de atividade física da população adulta das capitais brasileiras entre 2006 e 2013. Foram analisados os dados do Sistema de Vigilância de Fatores de Risco e Proteção para Doenças Crônicas por Inquérito Telefônico (VIGITEL), referentes aos anos de 2006 a 2013 em uma amostra anual de cerca de 54.000 adultos n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
1
29

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 21 publications
(32 reference statements)
4
14
1
29
Order By: Relevance
“…The current study showed that men practice physical activity in their leisure time approximately 50% more than women in Brazil. However, the trend remained stable among males and increased in females, which differs from previous studies 34 .…”
Section: Discussioncontrasting
confidence: 99%
“…The current study showed that men practice physical activity in their leisure time approximately 50% more than women in Brazil. However, the trend remained stable among males and increased in females, which differs from previous studies 34 .…”
Section: Discussioncontrasting
confidence: 99%
“…However, the reduction of total sedentary time and small changes in work routine such as discontinuation of sedentary behavior (e.g pauses for short stretches) can provide health benefits for workers 18,19 . According to an experimental research conducted by Alkhajah et al 20 , the introduction of a sitting / standing workstation can substantially reduce the sitting time of office workers both in the workplace and throughout the week.…”
Section: Discussionmentioning
confidence: 99%
“…Cad. Saúde Pública 2019; 35 (2):e00008618 dessas políticas 18,19 . Todavia, é necessário salientar que todas as políticas recentes relacionadas com a promoção de saúde, o que inclui as práticas corporais/atividade física, ainda estão em construção, algo natural dentro da proposição de conceitos e práticas de saúde populacional 21 .…”
Section: Figuraunclassified
“…Estudos nacionalmente abrangentes são baseados na descrição dos gestores, não relatando a percepção da população-alvo atingida 11,15,17 . Esse fato dificulta a avaliação do impacto dessas intervenções, visto que dados de tendências temporais demonstram que os níveis populacionais de inatividade física estão aumentando na população brasileira 18,19 , mesmo com todo o investimento que está sendo realizado.…”
Section: Introductionunclassified